NEW RECORD OF POLIS TES (POLIS TES) INDICUS STOLFA FROM INDIA (HYMENOPTERA : VESPIDAE: POLISTINAE) - KUMAR, P. GIRISH; KISHORE, LAMBERT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The species Polistes (Polistes,) indicuš Stolfa is reported for the first time from India and redescribed here.